2004
DOI: 10.1073/pnas.0307562100
|View full text |Cite|
|
Sign up to set email alerts
|

Myc-interacting protein 1 target gene profile: A link to microtubules, extracellular signal-regulated kinase, and cell growth

Abstract: To study the role of the transcription factor Myc-interacting protein 1 (MIZ-1) in activating various target genes after induction with the microtubule disrupting agent T113242, we have used small interfering RNA duplexes (siRNAs) to knockdown the expression of MIZ-1. As expected, depletion of MIZ-1 resulted in the inhibition of T113242-dependent activation of the low-density lipoprotein receptor (LDLR) gene in hepatocytes. Cells transfected with MIZ-1 siRNAs also exhibited growth arrest. In addition, inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
(17 reference statements)
1
14
0
Order By: Relevance
“…Controversially, Adhikary et al (2003) reported that Miz-1 is required for early embryonic development during gastrulation. Similarly, Ziegelbauer et al (2004) reported that the loss of Miz-1 by RNA interference caused cells to accumulate in G1 and led to inhibition of cell proliferation in HepG2 cells. These data indicate that Miz-1 may also have some functions in promoting cell survival or proliferation other than the function in arresting cell growth (Sakurai et al, 2004;Patel and McMahon, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…Controversially, Adhikary et al (2003) reported that Miz-1 is required for early embryonic development during gastrulation. Similarly, Ziegelbauer et al (2004) reported that the loss of Miz-1 by RNA interference caused cells to accumulate in G1 and led to inhibition of cell proliferation in HepG2 cells. These data indicate that Miz-1 may also have some functions in promoting cell survival or proliferation other than the function in arresting cell growth (Sakurai et al, 2004;Patel and McMahon, 2007).…”
Section: Discussionmentioning
confidence: 90%
“…4 Therefore, it appears likely that the essential Miz-1 target whose repression is necessary for c-Myc-induced apoptosis is among the many other genes activated by Miz-1. In fact, recent microarray analysis has revealed that a number of anti-apoptotic genes are activated by Miz-1 (22,23). These include BCL2, BCL2L1, MCL-1, and apoptosis inhibitor immediate early response 3 (IER3).…”
Section: Discussionmentioning
confidence: 99%
“…Following recruitment, Dnmt3a methylates surrounding DNA, yielding a closed chromatin state. Miz-1 regulates the expression of several hundred genes and initial studies suggest that many of these can be repressed by c-Myc (22,23). To date, detailed studies have been conducted primarily on Miz-1 targets of the cyclin-dependent kinase inhibitor class such as p15INK4b (CDKN2B) and p21CIP1 (CDKN1A) (12, 17-19, 24 -27).…”
mentioning
confidence: 99%
“…On the contrary, recent microarray experiments showed that after Miz-1 knockdown using small interfering RNAs, p21 levels were up-regulated. 1 Using multiple criteria, Ziegelbauer et al (26) showed that p21 may not be a bona fide Miz-1 target. Furthermore, in another context, where c-Myc was found to antagonize Ras-mediated induction of p21, it was shown that this effect was Miz-1 independent but relied on the inhibition of Sp1 transcriptional activity (27).…”
Section: P21mentioning
confidence: 99%